Age Bias in Time From Diagnosis Comparisons of Prostate Cancer Treatment. (April 2018) - Kendal, Wayne S.
Abstract : Objectives: Observational studies of prostate cancer treatment have demonstrated a major survival benefit with prostatectomy; randomized trials have been less certain in this regard. This discrepancy is hypothesized to be due to the use survival calculations based on time from diagnosis (TFD), which can bias toward better survival for younger cohorts. Attained age is an alternative timescale that can mitigate this effect. A Surveillance, Epidemiology and End Results comparison of prostatectomy, radiotherapy (XRT), and conservative management for localized prostatic cancer was conducted to compare these 2 timescales. Methods: Kaplan-Meier analysis was used to contrast overall survival based on TFD and attained age from 279, 064 prostate cancer cases. Proportional hazards models were constructed and baseline hazard functions estimated. Results: The prostatectomy cohort averaged 9 to 12 years younger than the radiotherapy or conservative management cohorts, and the baseline hazard depended more strongly upon age than TFD. Survival calculations based on TFD demonstrated a major benefit with prostatectomy compared with XRT and conservative management, consistent with prior observational studies. Calculations based on attained age, however, demonstrated lesser differences between treatment cohorts and were more consistent with published randomized trials. Conclusions: The survival benefit apparent to prostatectomy in conventional observational cohort studies could reflect an age-related bias attributable to their use of TFD analysis. Care is warranted in the choice of timescale in observational analysis if large age differences exist between treatment cohorts. Randomized controlled trials remain the most reliable means to compare prostate cancer treatments.